(untitled) (Contextos: Estudios de Humanidades y Ciencias Sociales, 2019)
In this essay I analyze Jerónimo López Mozo’s play, Yo, maldita india, as an example of historiographic metafiction that undermines the distinction between historical discourse and fiction as two autonomous genres. Thus, the play seems to suggest that History is not but staging –which denies the very existence of an authorial figure and historical facts that transcend the historical narration that recounts them—, a way of thinking prevalent in Spain since the transition to democracy. The notion of History as fiction is particularly interesting to college students even though its level of abstraction can make it extremely difficult to understand. Addressing it through a theatrical play allows students to achieve a better understanding of it while they develop an emotional connection toward the subject